ANALISIS KINERJA PROYEK SUTT 150 kV TAYAN - SANDAI TERHADAP ASPEK BIAYA DAN WAKTU DENGAN METODE EARNED VALUE - Sahat Josua Siahaan; Tri Wahyu Adi (Elektrika Borneo, 2026)
In a construction project, the key indicators of success are cost, quality, and time performance. To achieve these targets, proper planning, scheduling, and execution control are essential. The Earned Value concept is one of the integrated control methods used to manage both project cost and schedule effectively. This method is applied to analyze project performance and to forecast project completion by providing performance information at a specific reporting period and generating estimates for the total cost and time required to complete the entire project. This final project presents an analysis using the Earned Value Concept to evaluate the contractor's performance, as well as the cost and time aspects of the 150 kV Tayan – Sandai transmission line construction project. The project experienced delays caused by factors related to manpower, methods, materials, and the environment.